THE STUDENTS' MATHEMATICAL PROBLEM-SOLVING ABILITIES, SELF-REGULATED LEARNING, AND VBA MICROSOFT WORD IN NEW NORMAL: A DEVELOPMENT OF TEACHING MATERIALS - Citra Megiana Pertiwi; Euis Eti Rohaeti; Wahyu Hidayat (Jurnal Infinity, 2021)
The new normal period makes ICT-based education the spearhead of the implementation of learning. This becomes an obstacle and a challenge for students, especially in the mathematical problem-solving ability (MPSA), which is very important for students because it is a prior mathematical ability and is included in HOTS. Self-regulated learning in mathematics (SRL) also has a significant role in adapting to learning in the new normal and influences students' mathematical learning outcomes. However, the facts on the ground show that these two abilities are still low. To solve this problem, the researchers developed VBA Microsoft Word-based teaching materials on the relevant polyhedron materials for use so that learning would be more optimal. The method used in this research is an experimental method with a pretest-posttest control group design. The population is all the students in Cimahi City, while the sample is two classes randomly selected. This study indicates that VBA Microsoft Word-based teaching materials are appropriate to be applied in the new normal period, as indicated by the results of the achievement and improvement of MPSA and SRL of students is better than ordinary learning. There is an association between MPSA and SRL and positive response even though they still have difficulty making mathematical models on MPSA questions. Students are more enthusiastic in learning and don't get bored quickly; in line with the challenges of the new normal, the industrial revolution 4.0, and the learning curriculum, learning is more structured, interactive, effective, and efficient.